2013
DOI: 10.1016/j.freeradbiomed.2013.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive microRNAs—role in endothelial responses to shear stress and redox state

Abstract: Endothelial functions are highly regulated by imposed shear stress in vivo. The characteristics of shear stress determine mechanotransduction events that regulate phenotypic outcomes including redox and inflammatory states. Recent data indicates that microRNAs (miRs) in vascular endothelial cells (ECs) play an essential role in shear stress-regulated endothelial responses. More specifically, athero-protective pulsatile flow (PS) induces miRs that inhibit mediators of oxidative stress and inflammation while pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
97
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 106 publications
0
97
0
Order By: Relevance
“…Epigenetic modulations, including histone modification and RNA-based mechanisms, have been identified to regulate vascular functions (2)(3)(4). Histone deacetylases (HDACs) and microRNAs (miRs) have emerged as two important epigenetic mediators in vascular pathophysiology (2)(3)(4)(5)(6). In previous work, we demonstrated that exposure of ECs to OS induces associations of HDAC-3/5/7 with myocyte enhancer factor-2 (MEF-2) to down-regulate the antiinflammatory gene Krüppel-like factor-2 (KLF-2).…”
mentioning
confidence: 99%
“…Epigenetic modulations, including histone modification and RNA-based mechanisms, have been identified to regulate vascular functions (2)(3)(4). Histone deacetylases (HDACs) and microRNAs (miRs) have emerged as two important epigenetic mediators in vascular pathophysiology (2)(3)(4)(5)(6). In previous work, we demonstrated that exposure of ECs to OS induces associations of HDAC-3/5/7 with myocyte enhancer factor-2 (MEF-2) to down-regulate the antiinflammatory gene Krüppel-like factor-2 (KLF-2).…”
mentioning
confidence: 99%
“…Conversely, the decreased expression of eNOS in HUVEC exposed to acute hypoxia is controlled by the overexpression of a natural cis-antisense noncoding RNA called sONE [68] and changes in histone PTM which occur specifically at the promoter of eNOS [69]. Similarly, in the endothelium, hypoxia and oxidative stress regulate the expression of several miRNAs that modify the expression of eNOS and other enzymes related to its short-and long-term function [70]. In support of this notion, we have recently demonstrated that eNOS-induced NO enhances arginase-2 expression by epigenetic modifications in the histones residing at ARG2 gene promoter [71].…”
Section: Epigenetics In Endothelial Physiologymentioning
confidence: 99%
“…Thus, it has been proposed that miR-21 has a dual effect on vascular function: over a short time, it protects against hypoxia and ischemia [70,[102][103][104], and over the longer term, leads to endothelial dysfunction, apoptosis [70,102,105,106], and eNOS dysfunction. The latter would occur by targeting the expression of antioxidant enzymes [70], as well as enhancing the levels of the endogenous eNOS inhibitor asymmetric dimethyl arginine (ADMA) by downregulating the expression of the enzyme dimethyl arginine dimethylaminohydrolase 1 (DDAH1) [105,107,108]. These data suggest that the dynamic regulation of miR-21 and miR-126 could participate in the early defense of the endothelium to hypoxia and oxidative stress; nonetheless, they prime endothelial dysfunction over the long term.…”
Section: Potential Role Of Hypoxia-induced Mirnas Mir-21 and Mir-126mentioning
confidence: 99%
“…6,56,113 Given that FSS patterns are major physiological and pathophysiological stimuli that induce or suppress an array of pro-and anti-inflammatory genes in EC, it is likely that mechanosensitive micro-RNAs are involved in the regulation of endothelial redox and inflammatory phenotype. 114,115 Micro-RNA expression profiles have been shown to be differentially regulated in EC exposed to laminar and oscillatory FSS patterns, [116][117][118] leading to alterations in both pro-and anti-inflammatory gene expression, and thus may constitute an additional factor that contributes to atherogenesis. 119 For example, miR-92a has been shown to be downregulated in HUVEC exposed to US leading to enhanced Klf2 levels and hence expression of eNOS.…”
Section: Regulation Of Nrf2 By Micro-rnas In Endothelial Responses Tomentioning
confidence: 99%
“…Additional studies are necessary for the identification of mechanosensitive redoxi-miRs and elucidation of the mechanisms by which they regulate Nrf2/ARE signaling and antioxidant gene expression in EC exposed to FSS to fully assess the potential of micro-RNAs as therapeutic targets to prevent or treat atherosclerosis. [112][113][114]119 The evidence linking Nrf2 signaling to FSS patterns is unequivocal and mediated by a change in EC redox status, resulting in enhanced antioxidant gene induction thereby maintaining redox homeostasis. The likely regulation of key mediators of the Nrf2 pathway by redoxi-miRs 113 and mechanosensitive micro-RNAs, as well as potentially long noncoding RNAs, 129 add an additional dimension to provide fine tuning of EC redox signaling (Figure 2).…”
Section: Regulation Of Nrf2 By Micro-rnas In Endothelial Responses Tomentioning
confidence: 99%